2005
DOI: 10.1063/1.1968421
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic tunable dye laser with integrated mixer and ring resonator

Abstract: We report on results of design and fabrication of a microfluidic dye laser that consists of a ring resonator, a waveguide for laser emission output, and microfluidic elements for flow control, all integrated on a chip. The optical resonator and the waveguide were obtained by photolithography, whereas microfluidic elements such as channels, valves, and pumps were fabricated by multilayer soft lithography. As results, the prototype device worked with a few nanoliters of Rhodamine 6G dye molecules in ethanol solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 13 publications
0
71
0
Order By: Relevance
“…However, very few demonstrations along this line have appeared so far. Galas et al (2005) and Li et al (2007) have demonstrated the integration of PDMS-based soft microfluidics with optofluidic dye lasers to change the laser properties. Such integration can also be used to build sensing and spectrometer devices.…”
Section: Integration With Other ''Lab-on-a-chip'' Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very few demonstrations along this line have appeared so far. Galas et al (2005) and Li et al (2007) have demonstrated the integration of PDMS-based soft microfluidics with optofluidic dye lasers to change the laser properties. Such integration can also be used to build sensing and spectrometer devices.…”
Section: Integration With Other ''Lab-on-a-chip'' Functionsmentioning
confidence: 99%
“…Shortly after the demonstration of the first optofluidic dye laser, tunable output was obtained by index and concentration tuning (Bilenberg et al 2003;Galas et al 2005;Gersborg-Hansen and Kristensen 2007). An ultrawide mechanical tuning range was achieved with the soft PDMS-based optofluidic DFB dye lasers (Li et al 2006a, b).…”
Section: Tunable and Multiple Color Outputmentioning
confidence: 99%
“…Typically, the problem of dye bleaching is addressed by employing a continuous convective flow of liquid-dissolved dye molecules, compensating the bleaching dynamics caused by the external optical pump. In optofluidic dye lasers, the required convective dye-replenishing flow has been achieved by external fluid-handling apparatus ͑syringe pumps͒, 4-8 an on-chip microfluidic pump, 11 or by means of capillary effect. 9,12 In this letter we demonstrate that such optofluidic devices may potentially be operated for days by diffusion without the need for a convective flow.…”
mentioning
confidence: 99%
“…And compared to solid state dye lasers, microfabricated liquid dye lasers don't suffer from the photobleaching problem because the dye solution can be continuously replaced. Several groups have demonstrated such on chip dye lasers using different materials and laser cavities [1,2,3]. Tunable output was also obtained using concentration or index tuning methods [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have demonstrated such on chip dye lasers using different materials and laser cavities [1,2,3]. Tunable output was also obtained using concentration or index tuning methods [3,4]. Such on-chip liquid dye lasers are an example of the newly emerging optofluidic devices [5], in which the integration with microfluidics and the adaptive nature of liquid materials enable unique features that are not obtainable with solid state materials.…”
Section: Introductionmentioning
confidence: 99%